(untitled) (Research, Society and Development, 2022)
Endodontic treatment is based on chemical-surgical preparation, which includes cleaning, shaping and irrigation of the root canal system, in addition to three-dimensional endodontic filling. These fundamentals, when raised satisfactorily, fulfill their goals, which have to correct the scarring and repair of periapical tissues, thus keeping the tooth in the oral cavity. In this sense, intraoperative irrigation of the root canal system plays an important role in the success of endodontic therapy. Several techniques were corrected to perform this operative step, including: convencional irrigation, PUI and vacuum. Thus, the objective of the article is to review the current knowledge about the process of intraoperative endodontic irrigation under negative pressure (vacuum). For this, ​​with databases from Scielo, Bireme, Lilacs and Medline were used, with “endodontic”, “Irrigation”, “negative-pressure” and “endovac” as descriptors. 81 articles were found, of which 14 were used and the others were excluded for not meeting the exclusion criteria. Upon review, it is noted that endodontic irrigation changes satisfactory results, being predictable for use during endodontic therapy.